The association between body fat composition and urinary stone disease in the different community-based sex populations - FAN Xiao-hong; YE Wen-ling; MA Jie; SUN Ying; WANG Liang; DAI Qing; HENG Wei; ZHOU Ya-li; ZHANG Xue-he; SUN Wei; CUI Rui; ZHANG Wei; et al. (Linchuang shenzangbing zazhi)
Objective To investigate the association between body fat composition and urinary stone disease(USD) in different community-based sex populations.Methods The study was based on the cross-sectional survey performed in Pinggu District,Beijing in 2014.One thousand eight hundred and thirty-five participants in the survey were included in this study.All the subjects received interview for a questionnaire and somatological index measurement,and volunteered to take a 24-hour urine sample for determination of serum creatinine,blood urea,electrolytes and so on.Diagnosis of USD was identified by renal ultrasonic examination.The body composition analysis was performed with bioelectrical impedance measurement and a body composition analyzer(InBody720).Based on tertiles of the body fat percentage(BFP),the female and male subjects were divided into the low,medium and high body fat groups,respectively.Result In the present study,1730 participants were included in the final analysis.The mean age was 54.9±8.8 years,and 46.3% were males.The USD prevalence which ultrasonography proved was 7.0%.In all subjects and males,the prevalence of USD increased in parallel with BFP(P trend <0.05).The male had a odds ratio(OR) 2.63 times that of the females( 95%CI 1.77～3.92).In the male subjects,increase of BFP was significantly correlated with increase of the USD prevalence.In the multivariate logistic regression,the OR in the high BFP group was 1.98 times that in the low BFP group(95%CI 1.07～3.69),although there was no significant association between higher BFP and risk of USD in the female subjects. Conclusion In the male population in a common community,increase of BFP is associated with USD risk.Obesity measures,especially higher BFP,may help reduce USD risk,positively associated with a high risk of USD in males,but further studies are required to prove it.